Lipoperoxidation Is Selectively Involved in Progressive Supranuclear Palsy - Patrizio Odetti; Silvano Garibaldi; Raffaella Norese; Giovanna Angelini; Lucio Marinelli; Sabina Valentini; Stefano Menini; Nicola Traverso; D Zaccheo; Sandra L. Siedlak; George Perry; Mark A. Smith; et al. (2000)
Progressive supranuclear palsy (PSP) is a neurodegenerative disorder characterized by extensive neurofibrillary tangle (NFT) formation and neuronal loss in selective neuronal populations. Currently, no clues to the biological events underlying the pathological process have emerged. In Alzheimer disease (AD), which shares with PSP the occurrence of NFTs, advanced glycation end products (AGEs) as well as oxidation adducts have been found to be increased in association with neurofibrillary pathology. The presence and the amount of lipid and protein oxidation markers, as well as of pyrraline and pentosidine, 2 major AGEs, was assessed by biochemical, immunochemical, and immunocytochemical analysis in midbrain tissue from 5 PSP cases, 6 sporadic AD cases, and 6 age-matched control cases. The levels of 4-hydroxynonenal (HNE) and thiobarbituric acid reactive substances (TBARS), 2 major products of lipid peroxidation, were significantly increased by 1.6-fold (p < 0.04) and 3.9-fold (p < 0.01), respectively, in PSP compared with control tissues, whereas in AD only TBARS were significantly increased. In PSP tissue the intensity of neuronal HNE immunoreactivity was proportional to the extent of abnormal aggregated τ protein. The amount of protein oxidation products and AGEs was instead similar in PSP and control tissues. In AD, a higher but not significant level of pyrraline and pentosidine was measured, whereas the level of carbonyl groups was doubled. These findings indicate that in PSP, unlike in AD, lipid peroxidation is selectively associated with NFT formation. The intraneuronal accumulation of toxic aldehydes may contribute to hamper τ degradation, leading to its aggregation in the PSP specific abnormal filaments.